2017
DOI: 10.18410/jebmh/2017/436
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Clinicopathological Spectrum of Ovarian Tumours in a Tertiary Care Centre

Abstract: BACKGROUND Ovarian cancer is the 6 th most common cancer in worldwide among female population, whereas in India, it is the third most common cancer among women, 1 in 70 women have their lifetime risk to develop this tumour. Survival rate depends on the stage of diagnosis. Although, geographic and racial differences in the incidence of ovarian tumours are well-recognised information regarding any dissimilarity in clinicopathological behaviour is scarce. In the present study, the clinicopathological features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Incidence of bilaterality in tumours was 20.93% which compares well with other studies. 8,14,15 Neoplastic lesions (61.25%) were more than nonneoplastic lesions (38.75%). Among non-neoplastic lesions, Follicular cysts (67.7%) constituted the majority followed by corpus luteal cysts and endometriotic cysts Similar findings have been reported in other studies with follicular cysts making up 51-74.6% of non-neoplastic lesions.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Incidence of bilaterality in tumours was 20.93% which compares well with other studies. 8,14,15 Neoplastic lesions (61.25%) were more than nonneoplastic lesions (38.75%). Among non-neoplastic lesions, Follicular cysts (67.7%) constituted the majority followed by corpus luteal cysts and endometriotic cysts Similar findings have been reported in other studies with follicular cysts making up 51-74.6% of non-neoplastic lesions.…”
Section: Discussionmentioning
confidence: 97%
“…All these compare well with other studies. 17,18,19,16,20 Among germ cell tumours, all represented mature cystic teratoma. Sex cord stromal tumours seen in this study were granulosa cell tumours only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most ovarian tumors cannot be distinguished confidently on the basis of their clinical or gross characteristics alone. 2 Dilemma of differentiating a benign from a malignant tumour always exists by clinical examination. Imaging by USG though helps to locate origin size, consistency of tumour but diagnosis of malignancy in ovarian tumour by USG, CA125, MRI and other method is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they concluded that early diagnosis and prompt treatment can definitely reduce the mortality from ovarian tumour. 2…”
Section: Introductionmentioning
confidence: 99%